2002
DOI: 10.1046/j.1440-1819.2002.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between regional cerebral blood flow and the Wisconsin Card Sorting Test in negative schizophrenia

Abstract: The purpose of this study was to explore the relationship between regional cerebral blood flow (rCBF) and problem-solving thinking in negative schizophrenia. Twenty-one negative schizophrenic patients and 12 normal controls were studied with single photon emission computed tomography (SPECT). Measures of regional cerebral blood flow (rCBF) were taken both at rest and during a prefrontal activation task using Wisconsin Card Sorting Test (WCST). Compared with controls, poor performances on the WCST of total tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 23 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…The frontal cortex has been pointed out as a structure typically altered in schizophrenia [41] and has been suggested as a possible substrate of this relationship, having been associated with both executive function deficits [42] and negative symptoms [43,44] . Thus, Liu et al [45] found that schizophrenic patients with predominantly negative symptoms exhibited a lower regional cerebral blood flow change rate in the prefrontal lobe during stimulant WCST than normal control subjects. More recently, Moreno-Iniguez et al [46] found a relationship between low frontal blood flow at rest and negative symptoms such as difficulty in abstract thinking and lack of spontaneity and flow of conversation, as well as an association between affective blunting and low left-frontal blood flow during activation with the WCST.…”
Section: Discussionmentioning
confidence: 99%
“…The frontal cortex has been pointed out as a structure typically altered in schizophrenia [41] and has been suggested as a possible substrate of this relationship, having been associated with both executive function deficits [42] and negative symptoms [43,44] . Thus, Liu et al [45] found that schizophrenic patients with predominantly negative symptoms exhibited a lower regional cerebral blood flow change rate in the prefrontal lobe during stimulant WCST than normal control subjects. More recently, Moreno-Iniguez et al [46] found a relationship between low frontal blood flow at rest and negative symptoms such as difficulty in abstract thinking and lack of spontaneity and flow of conversation, as well as an association between affective blunting and low left-frontal blood flow during activation with the WCST.…”
Section: Discussionmentioning
confidence: 99%
“…11 In participants with schizophrenia, functional magnetic resonance imaging (fMRI) studies reported reduced activation of the prefrontal cortex during WCST performance, 12,13 and hypofrontality was described as the most salient activation difference in patients with schizophrenia compared with controls in single-photon emission computed tomography studies. 14 To the best of our knowledge, this study is the first to use event-related fMRI to investigate activation patterns during different subcomponents of the WCST in patients with schizo phrenia and healthy controls. Rule generation and selection have been proposed as elements of executive functioning with a well-founded basis in cognitive neuroscience research.…”
Section: Introductionmentioning
confidence: 94%
“…Replication of reduced relative frontal activity (Ingvar and FranzĂ©n, 1974), in the DLPFC during executive tasks, has been frequent in the past two decades, and has been observed in medicated, medication-free, and medication-naĂŻve patients (Barch et al, 2001; Barch et al, 2003; Berman et al, 1992; Berman et al, 1986; Callicott et al, 1998; Camchong et al, 2006; Cannon et al, 2005; Cantor-Graae et al, 1991; Carter et al, 1998; Catafau et al, 1994; Curtis et al, 1998; Driesen et al, 2008; Fletcher et al, 1998; Glahn et al, 2005; Goldberg et al, 1990; Liu et al, 2002; Mcdowell et al, 2002; Meyer-Lindenberg et al, 2002; Meyer-Lindenberg et al, 2001; Parellada et al, 1998; Parellada et al, 1994; Perlstein et al, 2001; Perlstein et al, 2003; Ragland et al, 1998; Rubia et al, 2001; Rubin et al, 1994; Schlösser et al, 2007; Steinberg et al, 1996; Volz et al, 1997; Weinberger et al, 1986; Yurgelun-Todd et al, 1996). Furthermore, there is evidence that the DLPFC dysfunction as described in schizophrenia is not solely explained by attentional or global cognitive impairment (Berman et al, 1988), nor is it a result of neuropsychiatric illness, generally, as patients with major depression (Barch et al, 2003; Berman et al, 1993) and Huntington's (Goldberg et al, 1990) do not exhibit this finding.…”
Section: Executive Circuits Within the Frontal Lobesmentioning
confidence: 99%